2021
DOI: 10.1016/j.cryobiol.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

High cryo-resistance of SARS-CoV-2 virus: Increased risk of re-contamination at transplantation of cryopreserved ovarian tissue after COVID-19 pandemic

Abstract: Cryopreservation and re-transplantation of ovarian tissue after anticancer treatment is important medical technology. Today, during a pandemic, the risk of contamination of transplanted cells with SARS-CoV-2 virus is extremely high. Data about cryo-resistance (virulence and/or infectivity) of SARS-CoV-2 are limited. Analysis and systematization of literature data allow us to draw the following conclusions: 1) The cytoplasmic membrane of somatic cell, like envelope of corona viruses, consists of lipid bilayer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Researchers have shown that salt enhances the thermostability of viruses by increasing van der Waals forces( Meister et al., 2020 ). Although SARS-CoV-2, with a lipid envelope, is more tolerant to low temperatures than viruses without an envelope ( Yao et al., 2020 ; Isachenko et al., 2021 ), it still can freeze. Without cryoprotectants, the protein activity will be affected by the freezing and thawing rate, and the structural protein on the virus envelope may change due to freezing and thawing ( Cao et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown that salt enhances the thermostability of viruses by increasing van der Waals forces( Meister et al., 2020 ). Although SARS-CoV-2, with a lipid envelope, is more tolerant to low temperatures than viruses without an envelope ( Yao et al., 2020 ; Isachenko et al., 2021 ), it still can freeze. Without cryoprotectants, the protein activity will be affected by the freezing and thawing rate, and the structural protein on the virus envelope may change due to freezing and thawing ( Cao et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…A relevant risk in cryopreservation is the potential transmission of pathogens during preparation and cryopreservation procedures. Although, the transmission of pathogens in samples stored in fertility cryobanks has never been reported ( 21 ), the cryo-resistance of SARS-CoV-2 is extremely high ( 22 ). So it is important to understand and mitigate these risks through safety and precautionary measures.…”
Section: Discussionmentioning
confidence: 99%
“…For fertility preservation purposes, reproductive cells and tissues are treated with specific cryoprotectants and immersed in liquid nitrogen (LN2) at ultra-low cooling temperatures of −196 °C [ 68 , 69 , 70 ]. Due to its high protein structure and low water content, the SARS-CoV-2 virus has an increased cryo-resistance, being stable at 4 °C, reaching maximum viability [ 71 ]. It is known that due to the presence of cryoprotectants, viruses can survive the freezing and thawing procedures, and hence one of the main concerns surrounding FP was the possibility of SARS-CoV-2 indefinite survival in LN2 and transmission at the moment of fertility restoration [ 72 ].…”
Section: What Are the Issues That Might Hamper A Safe Oncofertility P...mentioning
confidence: 99%